E-016 Intracranial endoluminal waveform analysis to understand the underlying pathophysiology and quantify treatment effect: case illustration involving venous sinus stenosis. (12th July 2011) - Spiotta, A; Rasmussen, P; Moskowitz, S
Abstract : Introduction: Extracranial waveform analysis of both arterial and venous intravascular compartments is common. Any catheter with a fluid-filled lumen that is of sufficient inner diameter to support transducing a pressure waveform can provide information from the intravascular compartment from which it is derived. This methodology, when applied to the intracranial vasculature, may provide useful insights into a patient's specific pathophysiology. Additionally, such waveform analysis could provide feedback to assess the efficacy of a targeted intervention. We present our preliminary experience with a strategy of assessing the intracranial, endoluminal waveforms during a neurointervention. Methodology: A 21-year-old female presented with rapid neurological decline progressing to obtundation secondary to intracranial hypertension. Angiography demonstrated left transverse sinus (TS) occlusion with stenosis of the contralateral TS. Under roadmap visualization, an Echelon microcatheter was crossed over a microwire proximal ("upstream") to the stenosis involving the right TS. Waveform analysis was performed at this starting point and as it was pulled back to a location distal to the stenosis ("downstream"). Waveforms were captured with the Bedmaster software package (Excel Medical Solutions) which we have customized to integrate data acquisition from the angiography suite. Results: ICP was monitored with an intraparenchymal monitor (Camino, Integra Neurosciences, Plainsboro, New Jersey, USA) and measured 54–59 mm Hg, while mean arterial pressure (MAP) measured by an arterial line in the radial artery measured 93–94 mm Hg. Proximal to the stenosis, pressure readings of 68 mm Hg with a waveform that mirrored an attenuated ICP waveform. Distal to the stenosis, the waveform dampened and mirrored the central venous pressure measured at 3 mm Hg. Angioplasty alone did not result in a sustained improvement, at which point a balloon mounted stent was used at the stenosis. Following treatment of the lesion the waveform analysis was repeated at the same locations along the TS which had been previously monitored. Treatment of the lesion resulted in a decrease in ICP to 36–37 mm Hg. The pressure along the TS was now 44 mm Hg along the treated TS with resolution of the pressure gradient. Conclusion: A significant pressure gradient was identified across the stenotic lesion in the TS, verifying the pathophysiologic process to be venous hypertension from venous outlet obstruction. ICP significant improved following treatment of the lesion and elimination of the pressure gradient across the lesion, again verifying venous outlet obstruction to be the underlying etiology.